Kiwi's diary a journey of Beacon's Party of 136 from upper Perak to Pahang - Richardson, Douglas (Second world war in Malaysia, 2007)
This book is a personal diary Douglas Richardson, which records the day-to-day events between 22nd January 1945 and 3rd September 1945 covering a period of approximately six months.